Prevention of postoperative adhesion reformation by intermittent intrauterine balloon therapy: a randomised controlled trial. (18th July 2019) - Shi, X; Saravelos, SH; Zhou, Q; Huang, X; Xia, E; Li, TC
Abstract : Objective: To compare the efficacy of intermittent intrauterine balloon dilatation versus standard care in the prevention of adhesion reformation. Design: Single‐blind randomised controlled trial. Setting: Hysteroscopic Centre of a tertiary University Hospital. Population: Two hundred patients with moderate to severe (European Society for Gynaecological Endoscopy Grade ≥II) intrauterine adhesions who underwent hysteroscopic adhesiolysis. Methods: All participants were randomised to a balloon group or a control group postoperatively. The balloon group received intrauterine balloon dilatation therapy at 2 weeks and 6 weeks after surgery, whereas the control group did not. All patients underwent follow‐up hysteroscopy at 4 and 8 weeks postoperatively. Main outcome measures: The adhesion reformation rate and the Pictorial Blood Loss Assessment Chart scores were analysed. Results: A total of 191 patients successfully completed the study protocol (94 cases for the balloon group and 97 cases for the control group). According to hysteroscopic evaluation at the 8th week, the overall adhesion reformation rate was significantly lower in patients in the balloon group than patients in the control group (20.2% versus 40.2%, respectively; P < 0.05). There was also a significant increase in menstruation flow, as assessed by the Pictorial Blood Loss Assessment Chart score (30 versus 9, respectively; P < 0.001). Conclusions: Postoperative intermittent intrauterine balloon dilatation therapy can significantly reduce postoperative adhesion reformation and significantly increase menstruation flow. Tweetable abstract: RCT: Postoperative intermittent intrauterine balloon therapy can prevent adhesion reformation after hysteroscopic adhesiolysis. Abstract : Tweetable abstract RCT: Postoperative intermittent intrauterine balloon therapy can prevent adhesion reformation after hysteroscopic adhesiolysis.